IMPACT OF HEADWATER HYDROLOGICAL DEFICIT ON THE DOWNSTREAM FLOOD‐BASED FARMING SYSTEM IN NORTHERN ETHIOPIA. (12th February 2020) - Negash, Emnet; Gebresamuel, Girmay; Embaye, Tesfa‐alem; Nguvulu, Alick; Meaza, Hailemariam; Gebrehiwot, Misgina; Demissie, Biadgilgn; Gebreyohannes, Tesfaalem; Nyssen, Jan; Zenebe, Amanuel
Abstract: Flood‐based farming is a means of improving crop production in rain‐deficit lowlands. Such spate irrigation systems are growing in importance, although the effects of headwater hydrological deficit on downstream flood farming are lacking evidence. This study investigates the impacts of headwater hydrological deficit on the extent of spate‐irrigated agriculture in the Guguf spate system. The length of canals and area of spate‐irrigated agriculture to the right and left of the Guguf River for the 1980s and 2010s were tracked using a global positioning system and mapped in a geographic information system interface, while climate data were collected from National Meteorological Agency. Trends of selected hydroclimatic variables were analysed using linear regression and the Pettitt test. The flash floods have shrunk by 7.36 × 10 6 m 3, as a result of which the length of canals and area of spate‐based farms declined by 1.37 km and 1540 ha, i.e. 35 and 57.5%, respectively, in only three decades. This corresponds to an average withdrawal of −44.0 ha yr‾¹. A single 1 million m 3 decline in flash floods caused a 366.4 ha decline in spate‐based farms. Moreover, farm fields located next to the river course are less affected, compared to those at the tail of the scheme. If the current trend continues, there is a high risk that the remaining farms currently receiving floods may find themselves outside of the spate systems. Therefore, we suggest that flood management technologies are needed to optimize the efficiency of soil moisture in the spate system. © 2020 John Wiley & Sons, Ltd. Résumé: L'agriculture fondée sur les inondations est un moyen d'améliorer la production agricole dans les plaines à déficit pluviométrique. Ces systèmes d'irrigation à crues gagnent en importance, bien que les effets du déficit hydrologique en amont sur l'agriculture par inondation en aval soient peu étudiés. Cette étude examine les impacts du déficit hydrologique en amont sur l'étendue de l'agriculture irriguée par crue dans le système de crues de Guguf. Les longueurs de canaux et les zones d'agriculture irriguée par crue à droite et à gauche de la rivière Guguf pour les années 1980 et 2010 ont été suivis à l'aide du système de positionnement global et cartographiés dans une interface de système d'information géographique, tandis que les données climatiques ont été recueillies auprès de l'Agence météorologique nationale. Les tendances pour certaines variables hydroclimatiques ont été analysées par régression linéaire et test de Pettitt. Les crues éclair ont été réduites de 7.36 × 106 m 3, en conséquence de quoi la longueur des canaux et la superficie des fermes à crue ont diminué de 1.37 km et 1540 ha, soit 35 et 57, 5%, respectivement, seulement en trois décennies. Cela correspond à un retrait moyen de −44.0 ha par an. Une baisse d'un million de mètres cubes des crues subites a entraîné une baisse de 366.4 ha dans les exploitations gravitaires. De plus, les champs situés à proximité du cours de la rivière sont moins touchés que ceux plus éloignés. Si la tendance actuelle se maintient, il existe un risque élevé que les autres fermes recevant actuellement des inondations soient épuisées. Par conséquent, nous suggérons que des technologies de gestion des inondations soient mises en œuvre pour optimiser l'efficacité de l'humidité du sol dans le système de crues. © 2020 John Wiley & Sons, Ltd.